Physarum polycephalum—a new take on a classic model system. (15th September 2017) - Oettmeier, Christina; Brix, Klaudia; Döbereiner, Hans-Günther
Abstract: Physarum polycephalum, literally the 'many-headed' slime mold, is a giant multi–nucleated but unicellular protist. Since the time of its first description, it has been the subject of a multitude of cell biological, biochemical, genetic, and lately physical studies. The enormous size of the cell, the easy method of in vitro cultivation, the unique life cycle and its highly visible internal cytoplasmic streaming have made it invaluable for investigations on cell cycle regulation, differentiation, cytoskeleton and locomotion. Research on P. polycephalum lost its prominent role when animal cell culture and genetic techniques became more advanced, thereby replacing the slime mold as a state-of-the-art model. However, research continued, driven by a small number of groups, resulting in full sequencing of the slime mold's genome, hence reviving interest in studying molecular processes that enable the astounding features of P. polycephalum . In recent years, research on P. polycephalum has again become cutting-edge. In 2000, Japanese researcher Toshiyuki Nakagaki performed a seminal experiment showing that the slime mold is able to find the shortest route through a maze. Ever since, smart problem-solving P. polycephalum has returned from the shadows and is nowadays back to center-stage when questions regarding the origins of intelligence and cognition are discussed. The basic mechanisms with which organisms perceive their environment, integrate this information and make decisions based on this input are investigated. The aim is to find underlying universal mechanisms of decision making and awareness. If those mechanisms can be found in as primordial an organism as a slime mold, it could fundamentally change our perception of the nature and evolution of cognition.